MARCUSCHI, L. A. (2007). Fenômenos da linguagem - Resende, Viviane de Melo (Revista Latinoamericana de Estudios del Discurso, 2020)
MARCUSCHI, L. A. (2007). Fenômenos da linguagem. Rio de Janeiro: Lucerna, 2007. 168p. ISBN 978-85-86930-63-8.